Anti-symmetric mode excitation and seismic response of base-isolated bridges under asynchronous input motion. Issue 113 (October 2018) - Papadopoulos, Savvas P.; Sextos, Anastasios G.
Abstract: This paper investigates the effect of asynchronous earthquake ground motion on the transverse response of base-isolated bridges. In this context, the excitation of anti-symmetric modes of vibration under asynchronous input is examined and is statistically correlated with characteristic engineering demand parameters. Different ground motion scenarios are considered for various combinations of soil class, wave propagation velocity and loss of correlation patterns among different support motions, using a spectral representation method to generate m-variate, fully non-stationary, EC8 spectrum-compatible ground motion vector processes. It is shown that in the idealised case of the wave passage effect only, the detrimental effects of asynchronous excitation are concentrated on the very last piers along the direction of the seismic waves. However, when loss of coherency is also taken into account in a more realistic scenario, the impact of spatial variability is significantly more uniformly distributed. Most importantly, the conditional probability of a detrimental increase in an EDP of interest (i.e., pier base bending moments and deck drift) under multi-support excitation given that an anti-symmetric mode is excited is not only uniform but also considerably high. This is a clear evidence that the local increase of seismic demand in the bridge studied is associated with the excitation of the first anti-symmetric mode of vibration. Highlights: Excitation of anti-symmetric modes under asynchronous seismic motion is investigated. Synthetic fully non-stationary EC8 spectrum compatible ground motions are generated. The excitation of higher modes is key in increasing seismic demand.